Penerapan Strategi Learning By Doing Dalam Meningkatkan Kecakapan Sosial Dan Intelektual Di Racana Wahid Hasyim Semarang - Sidqi, Kholfan Zubair Taqo (LP2M, 2020)
ABSTRACT The Scout Movement is Indonesian National Scout Organization as a non-formal educational institution that organizes scouting education. The Scout Movement functions as an educational organization non-formal outside the school and outside the family and as a forum for fostering and developing students based on the Among System by applying the Scouting Basic Principles and Scouting Methods. Furthermore, the aims and objectives of coaching in the Higher Education Gudep emphasize more on the character development of students and the implementation of Higher Education Tridarma through scouting activities. Not solely for the benefit of the nation and state but scouting in Higher Education there is a concrete phenomenon in the active contribution of, by, and for the future of the Cluster itself. Social development and intellectuals with the